PENTOSAN POLYSULPHATE INFLUENCEON THE COURSE OF CHRONICKIDNEYDISEASE ST'. II - IV - O. Dudari; M. Shifrisi; V.Ye. Driyanska; V.F. Krot; O.M. Loboda; K. Krasiuke; M.H. Krylova; Alexeeva N.G.; T.P. Bryzhachenko (Ukrainian Journal of Nephrology and Dialysis, 2015)
The aim is to determine the effect of the drug pentosan polysulphate at the rate of disease progression in patients with CKD II - IVst., to confirmation of lipid - lowering action and setting of the drug on indicators of chronic inflammation.Materials and methods. Tests conducted in one center for 12 weeks. The study included 60patients with CKD II - IV st. Patients were divided into 2 groups: group 1 (basic) - 30patients in addition to standard therapy receiving study medication, pentosan polysulphate, group 2 - 30 patients received only standard therapy. The drug pentosan polysulphate was administered for 8 - weeks: 100 mg. a day intramuscularly or intravenously for 3 weeks, followed by oral administration of 50 mg two times a day. The survey studied the dynamics ofdaily proteinuria, GFR, lipids, indicators of tumor necrosis factor, IL - 18 and vascular endothelial growth factor (VEGF) before and after treatment (12 week observation).Results. It was found a significant decrease in total cholesterol and atherogenic ratio after 3 months of treatment in the study group, hypolipidemic effect is more significant than in the comparison group. The group used pentosan polysulphate proteinuria reduction was more pronounced, and was 65% against 38% in the comparison group. Pentosan polysulphate in the treatment ofCKDpatients in stages II - IV contributes to significant decrease in inflammatory cytokines (IL - 18 and TNF - a) in contrast to the comparison group.Conclusions. The use of pentosan polysulphate in the treatment of patients with CKD stages II - IV had positive effect on lipid metabolism. Purpose pentosan polysulphate patients with CKD stages II - IV contributes to a significant reduction of the daily proteinuria and eGFR improvement, reduces levels of inflammatory cytokines: IL - 18 and TNF - a.